Circuit theory extended: The role of speculation in crises - Neil Lancastle (Economics: The Open-Access, Open-Assessment E-Journal, 2012)
This paper asks why modern finance theory and the efficient market hypothesis have failed to explain long-term carry trades; persistent asset bubbles or zero lower bounds; and financial crises. It extends Godley and Lavoie (Monetary Economics: An Integrated Approach to Credit, Money, Income, Production and Wealth, 2007) and the Theory of the Monetary Circuit to give a mathematical representation of Minsky's Financial Instability Hypothesis. In the extended circuit, the central bank rate is not neutral and the path is non-ergodic. The extended circuit has survival constraints that include a living wage, a zero interest rate and an upper interest rate. Inflation is everywhere. The possibility of stable carry trades emerges. In high interest rate, hedge economies, powerful banks invest surplus loan interest. With speculation, banks lobby to enter investment markets and the system is precariously liquid/illiquid. In a Ponzi economy, where loans never get repaid, solvency is a balance between increasing reserves, reducing interest rates and rebuilding banks' balance sheets during systemic crises. Simulating bank bailouts, household bailouts and a Keynesian boost suggests that bank bailouts are the least effective intervention, exerting downward pressure on wages and household spending: austerity.
Keywords: E10; E27; E43; E58; E60; 330; circuit theory; macroeconomic simulation; carry trade; austerity; banking regulation; interest rate policy; Finanzmarktkrise; Wirtschaftliche Instabilität; Geldtheorie; Geldumlauf; Wertpapierspekulation; Bankenpolitik; Zinspolitik; Theorie